Is multiple object tracking carried out automatically by an early vision mechanism independent of higher-order cognition? An individual difference approach. - Oksama, Lauri; Hyönä, Jukka (Visual Cognition, 2004)
Existing theories of multiple object tracking (MOT) offer different predictions concerning the role of higher level cognitive processes, individual differences, effortful attention and parallel processing in MOT. Pylyshyn's model (1989) argues for an automatic parallel processing mechanism separate from other cognition, whereas alternative models (e.g., Kahneman & Treisman, 1984 or spotlight models) are based on higher level cognition such as spatial short-term memory and/or effortful attention switching. These predictions were examined in Experiment 1 where identical objects and in Experiment 2 where visually and semantically distinct objects were tracked. Both experiments demonstrated a substantial individual variation in the estimated tracking capacity. Tasks measuring visuospatial short-term memory and attention switching proved to be significant predictors of MOT. In addition, tracking performance deteriorated as a function of tracking time and set size. Our results are in contrast to Pylyshyn's model. A mechanism with both parallel and serial processing and temporary spatial memory is outlined to accommodate the observed pattern of results.